Shiga toxin-producing Escherichia coli illness in Aotearoa | New Zealand, 2016-2022: epidemiological, genomic and traditional typing analyses provide insight into a significant endemic disease while highlighting knowledge gaps - Wright, Jacqueline; Duncan, David; Strydom, Hugo; Paine, Shevaun; Jefferies, Sarah; de Ligt, Joep; Rivas, Lucia; Addidle, Michael; Cookson, Adrian L.; Winter, David; Miller, Hilary; Casey, Geraldine; et al. (Frontiers in Microbiology, 2025)
IntroductionShiga toxin producing Escherichia coli (STEC) cause significant endemic disease in Aotearoa | New Zealand (NZ) with a 2022 case incidence rate of 19.9/100,000 population. The introduction of culture independent diagnostic testing has been pivotal in elucidating STEC case numbers.MethodsEpidemiological data from 5,769 cases of STEC infection confirmed during the 7-year period 2016-2022 were reviewed in conjunction with epidemiological typing data from 3,746 case isolates (2,939 analyzed via whole genome sequencing).Results and discussionSevere illness was reported for 25% of all STEC cases, and 23% of cases were hospitalized. All age groups were affected, but the greatest level of morbidity was observed in those less than 5 years old where the hemolytic uremic syndrome (HUS) incidence rate was 2.86/100,000. Serotypes O157:H7 and O26:H11 together accounted for 54% of infections. Other common serotypes differed from those reported as common elsewhere and included O128:H2, O38:H26, O146:H21 and O91:H14. Shiga toxin subtype 2a strains were more associated with serious illness than other subtypes, regardless of eae positivity. Multiple STEC strains were inadvertently identified in 1.2% of culture positive case samples suggesting that carriage of more than one strain could be more prevalent. Single nucleotide polymorphism (SNP) analysis indicated that most STEC cases were sporadic as 5-SNP genomic clusters were uncommon. Infection sources are rarely proven as food and environmental sample data are limited and insufficient to assist in determining pathways to infection. By combining isolate WGS-derived typing data and case epidemiological data we demonstrated the importance of shifting the focus from a select number of STEC serogroups to composite seropathotypes—based on full serotype, ST, cgMLST relatedness and stx sub-toxin profile—to assist in understanding both the role of each type in disease severity, and relationships across historical type groups. This knowledge may be useful in future prioritizing of clinical and public health resources.